Epigenetic regulator ARID1A and stem cell transcription factor SOX9 in the maintenance of pancreatic ductal cell differentiation state and development of intraductal papillary mucinous neoplasia (IPMN) and pancreatic ductal adenocarcinoma (PDAC) - Cui, Naipeng; Zhang, Jinsong; Huang, Huatian; Lu, Lingeng (Translational Cancer Research, 2018)
Pancreatic ductal adenocarcinoma (PDAC) is one of the highest mortality malignancies, with average 5-year survival less than 3%.